Efecto de fosfitos de potasio y calcio sobre la calidad poscosecha en duraznos cv. Flordaking - Leone, Andrea Inés; Brambilla, Maria Virginia; Barbieri, Martin Osvaldo; Mitidieri, Mariel Silvina (Facultad de Ciencias Agrarias, Universidad Nacional de Jujuy, 2022)
Poster